Hands-On Training Improving Barista Competency: The Role Of Delivery Strategy - Chairul Razak; Agus Riyanto; Silitonga, Parlagutan; Sigit Dani Nugraha (Jurnal Ilmiah Hospitality Management, 2025)
A competent barista is needed, along with the increasing prevalence of coffee shops in Indonesia. This study aims to analyze the influence of training facility and training modules on participants' competencies mediated by delivery strategy. There are 212 respondents in a simple random technique to collect data by an accidental method. The PLS-SEM analysis method was applied using the Smart PLS 3.0 application. The results of the study showed that training facilities and delivery strategies have a direct effect on competent participants. Meanwhile, the training module does not directly influence competent participants. Training facilities and training modules have a direct effect on delivery strategies. Training facilities and training Modules affect competencies through delivery strategies. Delivery strategies have played a strong role in mediating the effect of training modules and competent participants that strengthen human resources in the hospitality industry. The researchers assumed that this is the contribution of this study since no such research has been conducted yet, in accordance with our observation